METHODS FOR THE IDENTIFICATION OF PATHOGENIC LISTERIA IN FOOD PRODUCTS - Eskendirova, S.Z.; Kaukabayeva, G.K.; Mukhlis, S.E.; Akhmetkarimova, Zh.S. (Eurasian Journal of Applied Biotechnology, 2025)
Listeriosis is an infectious disease that affects both humans and animals and is caused by Listeria monocytogenes. It is characterized by multiple sources of pathogen entry, a wide range of transmission routes and factors, polymorphic clinical manifestations, and high mortality rates. L. monocytogenes is considered a unique foodborne pathogen due to its intracellular lifecycle and remarkable adaptive capabilities. The pathogenesis of listeriosis is largely driven by the virulence factors of L. monocytogenes, which enable incomplete phagocytosis, intracellular parasitism, rapid host cell invasion, and the development of antibiotic resistance. These virulence determinants act at various stages of the host infection cycle, enhancing the pathogen’s ability to evade immune responses and establish persistent infections. Given the pronounced polymorphism of clinical manifestations and the unique biology of the pathogen, improving laboratory diagnostic methods and developing targeted immunoprophylactic strategies are of paramount importance. This article reviews recent advances in the epizootiology, epidemiology, and pathogenesis of listeriosis. It also highlights key pathogenicity and virulence factors of L. monocytogenes as critical targets for the development of rapid identification techniques in food products. The implementation of modern rapid detection methods significantly reduces analysis time and increases the accuracy of results, even when the pathogen is present in low concentrations within the tested samples.